PEMBELAJARAN PAK DI SEKOLAH DI APIT OLEH LAJUNYA KEMAJUAN PENGETAHUAN SERTA TEKNOLOGI PENDIDIKAN MODERN (Sebuah tindakan pro aktif untuk masa depan guru PAK di sekolah) - Jack Wenno (Institut Agama Kristen Negeri (IAKN) Ambon, 2021)
Abstract: Teachers are said to be professional and modern, not because they are considered inspiring and innovative, but because they are required to be innovative, creative, inspiring, pro-active, and modern. Modern teachers mean quality and master various technologies in general and in particular. General, means mastering various technological results. And specialize in mastering various educational technologies (various educational media). This study aims to see how PAK teachers can become multi-talented future teachers for their students. The research method uses combination research, namely the mixed method. Based on the results of the study, it was found that to measure a professional and modern PAK teacher, it is not only measured from the teacher being an inspiring, motivated, multitalented teacher but also being a teacher who can manage classes with PAIKEM GEMBROT nuances and learning combined with various media sources. learning based on visual, audio-visual, computer, computer and interactive video, Microsoft PowerPoint, and the internet. Keywords : PAK learning in schools,advances in knowledge,educational technology